Projeto experimental : Corrente do Bem - Cruz, Camila de Almeida da (2018)
This project deals with the communication difficulties of the group Corrente do Bem, which works with volunteer activities in communities, in the city of Passo Fundo, Rio Grande do Sul. To solve these problems in communication, we sought to analyze the current image of the The internal factors, which were conducted two unstructured qualitative interviews with the organizers of the group, and external factors, conducting semi-structured interviews with professionals and the target audience, located in neighborhoods of the city of Passo Fundo, with This will seek to provide new communication strategies to the group, as well as a new visual identity manual, producing a communication campaign to the group Corrente do Bem, which will be published in 2019. With this project, it is possible to see the importance of these social actions carried out by the Current of Good, and the possible possibilities for the media to reach communi adhesion, it is concluded that creating and implementing a campaign without money is a complicated path, but it generates motivation to find alternatives and partnerships so that everything goes well and communication goals are achieved.